2015
DOI: 10.1523/jneurosci.0919-15.2015
|View full text |Cite|
|
Sign up to set email alerts
|

Progressive, Seizure-Like, Spike-Wave Discharges Are Common in Both Injured and Uninjured Sprague-Dawley Rats: Implications for the Fluid Percussion Injury Model of Post-Traumatic Epilepsy

Abstract: Variable-duration oscillations and repetitive, high-voltage spikes have been recorded in the electrocorticogram (ECoG) of rats weeks and months after fluid percussion injury (FPI), a model of traumatic brain injury. These ECoG events, which have many similarities to spike-wave-discharges (SWDs) and absence seizures, have been proposed to represent nonconvulsive seizures characteristic of posttraumatic epilepsy (PTE). The present study quantified features of SWD episodes in rats at different time points after m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 83 publications
8
61
4
2
Order By: Relevance
“…We recently reported that epochs of SWDs and associated immobility are indistinguishable between FPI and sham-injured rats (Rodgers et al, 2015). We concluded that since their occurrence did not require prior injury, they must reflect heritable seizures typically reported in rats inbred for SWDs over multiple generations and used as genetic models of absence epilepsy for decades.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…We recently reported that epochs of SWDs and associated immobility are indistinguishable between FPI and sham-injured rats (Rodgers et al, 2015). We concluded that since their occurrence did not require prior injury, they must reflect heritable seizures typically reported in rats inbred for SWDs over multiple generations and used as genetic models of absence epilepsy for decades.…”
Section: Introductionmentioning
confidence: 83%
“…Whether SWDs reflect PTE has been challenged by evidence of an equal prevalence in age-matched uninjured rats (Pearce et al, 2014;Rodgers et al, 2015). We recently reported that epochs of SWDs and associated immobility are indistinguishable between FPI and sham-injured rats (Rodgers et al, 2015).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations